2015
DOI: 10.1088/0953-8984/27/4/046004
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction study of the (BiFeO3)1−x(PbTiO3)xsolid solution: nanostructured multiferroic system

Abstract: Neutron diffraction studies performed on the solid solution of (BiFeO(3))(1-x)(PbTiO(3))(x) reveal a mixture of two nanoscale phases with different crystal structures: a rhombohedral BiFeO(3)-based phase and a tetragonal PbTiO3-based phase. The ratio of Fe(3)+ and Ti(4)+ ions in the two phases is practically constant; only the proportion of the phases changes. The magnetic moments in the BiFeO(3)-based phase, in contrast to BiFeO(3), deviate from the basal plane. The temperature evolutions of the spin componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…Present study reveal that, introduction of 10% BiFeO 3 in Sr(Fe 0.5 Nb 0.5 )O 3 further enhances the ferromagnetic character. As shown in figure 1(a), the temperature dependence of dc magnetization M(T) of 0.1BF-0.9SFN ceramic has the lower temperature magnetic anomaly around ≈42 K. If we ignore the second magnetic anomaly in M(T) at 130 K, the shape of the M(T) plot is similar to that reported by Golosovsky et al [33] for the tetragonal (P4mm) phase of 0.5BiFeO 3 -0.5PbTiO 3 ceramic. They have reported a magnetic transition around 23 K which is accompanied by the distortion in crystal lattice as evidenced by appearance of anomaly in lattice parameter at the magnetic transition.…”
Section: Temperature Dependent Dc-magnetization M(t ) Studiessupporting
confidence: 82%
“…Present study reveal that, introduction of 10% BiFeO 3 in Sr(Fe 0.5 Nb 0.5 )O 3 further enhances the ferromagnetic character. As shown in figure 1(a), the temperature dependence of dc magnetization M(T) of 0.1BF-0.9SFN ceramic has the lower temperature magnetic anomaly around ≈42 K. If we ignore the second magnetic anomaly in M(T) at 130 K, the shape of the M(T) plot is similar to that reported by Golosovsky et al [33] for the tetragonal (P4mm) phase of 0.5BiFeO 3 -0.5PbTiO 3 ceramic. They have reported a magnetic transition around 23 K which is accompanied by the distortion in crystal lattice as evidenced by appearance of anomaly in lattice parameter at the magnetic transition.…”
Section: Temperature Dependent Dc-magnetization M(t ) Studiessupporting
confidence: 82%
“…Another possible source for the "rounding" of the phase transition could be a mutual interaction of wurtzite and zinc blende nanoparticles with different magnetic orders due to a well-developed interface between them. For example, magnetic proximity effects [30,44,45] between ZB-CoO, with a higher Néel temperature, and W-CoO could induce a magnetic order in the W-CoO. However, our neutron diffraction experiments with single phase wurtzite nanoparticles showed that although the diffraction signal was too weak to perform any quantitative calculations, the long-range magnetic order was unambiguously observed.…”
Section: Discussionmentioning
confidence: 71%
“…This indicates a strong anisotropic shape of the nanoparticles. The non-monotonic dependence of the peak broadening implies an "anisotropic size-effect", which is characteristic for diffraction of nanoparticles, whose shape cannot be well approximated by a sphere [29,30]. In this case, the "apparent size", i.e.…”
Section: Zinc Blende Coo Nanoparticlesmentioning
confidence: 99%
“…The same composition 0.7BiFeO 3 –0.3PbTiO 3 has been claimed to be a mixture of tetragonal P 4 mm and either rhombohedral R 3 c (ref. 44 ) or monoclinic Cc (ref. 35 ) structures.…”
Section: Discussionmentioning
confidence: 99%